The interaction of lubricin/proteoglycan 4 (PRG4) with toll-like receptors 2 and 4: an anti-inflammatory role of PRG4 in synovial fluid. Issue 1 (December 2015) - Alquraini, Ali; Garguilo, Steven; D'Souza, Gerard; Zhang, Ling; Schmidt, Tannin; Jay, Gregory; Elsaid, Khaled
Abstract Background Lubricin/proteoglycan-4 (PRG4) is a mucinous glycoprotein secreted by synovial fibroblasts and superficial zone chondrocytes. PRG4 has a homeostatic multifaceted role in the joint. PRG4 intra-articular treatment retards progression of cartilage degeneration in pre-clinical posttraumatic osteoarthritis models. The objective of this study is to evaluate the binding of recombinant human PRG4 (rhPRG4) and native human PRG4 (nhPRG4) to toll-like receptors 2 and 4 (TLR2 and TLR4) and whether this interaction underpins a PRG4 anti-inflammatory role in synovial fluid (SF) from patients with osteoarthritis (OA) and rheumatoid arthritis (RA). Methods rhPRG4 and nhPRG4 binding to TLR2 and TLR4 was evaluated using a direct enzyme linked immunosorbent assay (ELISA). Association of rhPRG4 with TLR2 and TLR4 overexpressing human embryonic kidney (HEK) cells was studied by flow cytometry. Activation of TLR2 and TLR4 on HEK cells by agonists Pam3CSK4 and lipopolysaccharide (LPS) was studied in the absence or presence of nhPRG4 at 50, 100 and 150 μg/ml. Activation of TLR2 and TLR4 by OA SF and RA SF and the effect of nhPRG4 SF treatment on receptor activation was assessed. PRG4 was immunoprecipitated from pooled OA and RA SF. TLR2 and TLR4 activation by pooled OA and RA SF with or without PRG4 immunoprecipitation was compared. Results rhPRG4 and nhPRG4 exhibited concentration-dependent binding to TLR2 and TLR4. rhPRG4 associated with TLR2- and TLR4-HEK cells in a time-dependent manner. Co-incubation of nhPRG4 (50, 100 and 150 μg/ml) and Pam3CSK4 or LPS reduced TLR2 or TLR4 activation compared to Pam3CSK4 or LPS alone (p <0.05). OA SF and RA SF activated TLR2 and TLR4 and nhPRG4 treatment reduced SF-induced receptor activation (p <0.001). PRG4 depletion by immunoprecipitation significantly increased TLR2 activation by OA SF and RA SF (p <0.001). Conclusion PRG4 binds to TLR2 and TLR4 and this binding mediates a novel anti-inflammatory role for PRG4.